2022
DOI: 10.1002/anie.202201220
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Aptamers with Selectively Enhanced Biostability in the Tumor Microenvironment

Abstract: Aptamers are emerging as promising molecular tools in cancer-targeted theranostics. Improving their in vivo stability has been a critical issue in promoting clinical translation, but such efforts could lead to more serious side effects resulting from prolonged retention in healthy organs. To address this problem, we developed an environment-responsive stabilization strategy for the selective enhancement of aptamer biostability in the tumor microenvironment (TME). Briefly, by means of the end extension of an AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
(5 reference statements)
0
12
0
Order By: Relevance
“…Therefore, we leverage the combination of two typical surface protein markers, CD63 for exosomal-specific markers and EpCAM for the tumor-specific marker, to set up an orthogonal screening threshold and recognize tumorderived exosomes from complicated biofluid samples precisely. Aptamers are promising tools for protein labeling because of their excellent specificity and affinity, low production costs, and configurational programmability [39][40][41] . We designed two allosteric aptamer probes of CD63 and EpCAM (detailed in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we leverage the combination of two typical surface protein markers, CD63 for exosomal-specific markers and EpCAM for the tumor-specific marker, to set up an orthogonal screening threshold and recognize tumorderived exosomes from complicated biofluid samples precisely. Aptamers are promising tools for protein labeling because of their excellent specificity and affinity, low production costs, and configurational programmability [39][40][41] . We designed two allosteric aptamer probes of CD63 and EpCAM (detailed in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, taking advantage of adenosine-rich characteristics of the tumor microenvironment, aptamer sequences that can respond to adenosine binding are designed for incorporation into functional NA sequences to specifically prolong their biostability in the tumor microenvironment. 127 In principle, functional NAs can be degraded by exonucleases in physiological conditions, predominantly starting from two free ends of NAs. But the specific incorporation of adenosine in the minor groove of the aptamer sequences could protect the NA strand from exonuclease digestion, which would prolong the stability of NAs in a complex environment.…”
Section: ■ Outlook and Perspectivementioning
confidence: 99%
“…In addition to the conventional modifications noted above, our recent study has focused on achieving the same goal without introducing external modifications. For instance, taking advantage of adenosine-rich characteristics of the tumor microenvironment, aptamer sequences that can respond to adenosine binding are designed for incorporation into functional NA sequences to specifically prolong their biostability in the tumor microenvironment . In principle, functional NAs can be degraded by exonucleases in physiological conditions, predominantly starting from two free ends of NAs.…”
Section: Outlook and Perspectivementioning
confidence: 99%
“…Aptamer-based drugs hold great promise in cancer-targeted therapy, but poor biostability caused by nuclease degradation limits their clinical applications. Tan group 38 demonstrated that the stability of aptamer will be greatly increased by linkage to an ATP aptamer, because the binding of ATP and its aptamer can protect the entire DNA strand from nuclease digestion, and the concentration of ATP in tumor cells is much higher than in normal cells, so the binding of ATP can greatly improve the stability of the aptamer.…”
Section: Targeted Accumulation Of Dna-based Drug Carriersmentioning
confidence: 99%